2023
DOI: 10.3389/fpubh.2023.1116583
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, chronic kidney disease, and mortality among older adults: A prospective study of National Health and nutrition examination survey, 1999–2018

Abstract: IntroductionPolypharmacy might contribute to a range of adverse outcomes, which could get worse in the elderly with chronic kidney disease (CKD). Evidence on polypharmacy, CKD, and mortality is scarce. We aimed to investigate the prospective association between polypharmacy, CKD and all-cause and cause-specific mortality in adults aged ≥65 years.MethodsA total of 13,513 adults from the National Health and Nutrition Examination Surveys were included, following up from 1999 to 2018 until December 31, 2019. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Compared to people without polypharmacy, polypharmacy was inclined to accelerate frailty states progression, leading to adverse clinical outcomes and a higher risk of mortality in older patients with frailty [ 22 ]. Our recent study also found that polypharmacy was associated with increased risks of all-cause and cardiovascular mortality among the elderly chronic kidney disease patients [ 8 ]. In real-world clinical settings, the majority of older adults suffered from multimorbidity and polypharmacy, though the use of multiple medications may treat symptoms effectively for multimorbidity, it is crucial to explore the clinical trajectories of individuals by focusing on the dynamics and complexities of multimorbidity and polypharmacy [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to people without polypharmacy, polypharmacy was inclined to accelerate frailty states progression, leading to adverse clinical outcomes and a higher risk of mortality in older patients with frailty [ 22 ]. Our recent study also found that polypharmacy was associated with increased risks of all-cause and cardiovascular mortality among the elderly chronic kidney disease patients [ 8 ]. In real-world clinical settings, the majority of older adults suffered from multimorbidity and polypharmacy, though the use of multiple medications may treat symptoms effectively for multimorbidity, it is crucial to explore the clinical trajectories of individuals by focusing on the dynamics and complexities of multimorbidity and polypharmacy [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of multiple medications may treat symptoms, prevent disease complications, or increase life expectancy, the majority of research suggests that polypharmacy is associated with negative clinical consequences, including nonadherence to treatment, adverse drug events (e.g., falls, fractures, renal failure), drug-drug interactions, and hospitalizations [ 5 , 6 ]. Polypharmacy is also linked to increased risks of disability, cognitive decline, and even mortality [ 7 , 8 ]. In addition, polypharmacy is ordinary among individuals with multimorbidity and an excess of unplanned hospitalizations is seen in those with higher levels of polypharmacy, leading to higher costs of care for individuals and health care systems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence indicates that polypharmacy is associated with adverse clinical outcomes, such as hospitalizations, medication–drug interactions, nonadherence to treatment, and adverse drug events (e.g., falls, fractures, and renal failure) [ 7 , 8 , 9 ]. Moreover, polypharmacy has been connected to higher chances of cognitive decline, disability, and death [ 5 , 10 ]. Furthermore, people with multimorbidity frequently experience polypharmacy, and those with many medications tend to have more unplanned hospitalizations [ 11 ], which drives up expenditures for both individuals and healthcare systems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…of comorbidities, polypharmacy, frailty, oxidative stress, and increased risk of myocardial and renal dysfunction. 12,13 Age is an important contributor to increasing comorbidities among PLWH. Data from the United States predicts that by 2030, nearly 50% of PLWH will have multiple comorbidities, with significant increases in CKD, dyslipidemia, diabetes, and myocardial infarction.…”
mentioning
confidence: 99%